DFT study on the regio- and stereo-selectivity of the Diels–Alder reaction between a cycloprop-2-ene carboxylate and some cyclic 1, 3-dienes. (1st June 2016) - Haghdadi, Mina; Nab, Nasim; Bosra, Hassan Ghasemnejad
A study of the reactivity and regio- and stereo-selectivity of Diels-Alder reactions of 2-methyl-3-propionylcycloprop-2-ene carboxylic acid methyl ester with cyclohexa-1, 3-diene derivatives and furan, in the gas phase, has been carried out using density functional theory (DFT)-based reactivity indices and activation energies. Four reaction channels associated with ortho (or meta), meta (or para), endo and exo pathways have been explored and characterised. The activation energies indicate that the endo pathways are preferred and DFT-based reactivity indices clearly predict the stereochemistry of the isolated cycloadducts.